Asymmetry of prosperity and business activity levels according to the regions of Georgia - Alim Kherkhadze (ეკონომიკური პროფილი)
The conditions in a specific region of Georgia serve as a key indicator of the country's overall economic, political, and social strength. This makes accurate analysis and effective problem-solving essential. Regions within Georgia face notable challenges, with varying development opportunities. To maximize impact, it's crucial to utilize each region’s development potential optimally and to allocate resources strategically. Georgia’s population distribution is uneven, with most residents concentrated in municipal centers and economically active areas. Regional disparities in development stem from natural-geographic characteristics and differing levels of industrial, tourism, agricultural, social, and infrastructure development.